PELAKSANAAN SELF ASSESMENT SYSTEM MENURUT PERSEPSI WAJIB PAJAK ORANG PRIBADI - Laila, Nur; Mustaqim, Mustaqim (Universitas Muhammadiyah Magelang, 2006)
The aim of this research is to investigate the empirical evidence about influence perception personal tax payer to bring about self assesment system. Self assesment system is system of tax collection that give to tax payer o calculate, to report, to Tx Servanter Office, and the deposite by him/hisself him/his taxses to Cash of State. This research was to examine whether are there influence perceptions between personal tax payer to bring about selt assesment system. The analysis is based on the answer from respondent where its data are gathered trough questionaires in which ita distribution at Magelang. The sample of this research are personality, who take from employee and official from governmental office. The respondents of this research are 40 respondents. Convenience sampling have used in this research. The method of analysis data are descriptive statistic, validity and reability, and regression, and partial t-test. Result showed that, the data in this research is valid and reliable. The results showed taht perception personal tax payer are influence to bring about self assesment system. The analysis perception personal tax payer to bring about self assesment system have influence with t-test 7.069 and p=0.000, p<0.05.